2020
DOI: 10.3390/ijms21176351
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Cell Dysfunction and Its Role in COVID-19

Abstract: When facing an acute viral infection, our immune systems need to function with finite precision to enable the elimination of the pathogen, whilst protecting our bodies from immune-related damage. In many instances however this “perfect balance” is not achieved, factors such as ageing, cancer, autoimmunity and cardiovascular disease all skew the immune response which is then further distorted by viral infection. In SARS-CoV-2, although the vast majority of COVID-19 cases are mild, as of 24 August 2020, over 800… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
132
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 131 publications
6
132
0
3
Order By: Relevance
“…Accordingly, the ratios of granulocytes/lymphocytes and granulocytes/CD3 + T cells were highly increased, and in both cases, the differences were statistically significant (5.16 vs. 2.02 of controls, p < 0.01 and 7.19 vs. 3.14 of controls, p < 0.01, respectively). Taken together, although the number of active COVID-19 patients included in this study was limited ( n = 11), the phenotypic changes in their WBC subpopulations detected herein are in agreement with published reports [ 21 , 22 , 23 , 24 ] and support the severe deficiency of both innate and adaptive immune responses in hospitalized patients with active COVID-19.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Accordingly, the ratios of granulocytes/lymphocytes and granulocytes/CD3 + T cells were highly increased, and in both cases, the differences were statistically significant (5.16 vs. 2.02 of controls, p < 0.01 and 7.19 vs. 3.14 of controls, p < 0.01, respectively). Taken together, although the number of active COVID-19 patients included in this study was limited ( n = 11), the phenotypic changes in their WBC subpopulations detected herein are in agreement with published reports [ 21 , 22 , 23 , 24 ] and support the severe deficiency of both innate and adaptive immune responses in hospitalized patients with active COVID-19.…”
Section: Resultssupporting
confidence: 92%
“…Using an in-house-designed 12-color flow cytometry panel, we immunophenotyped 24 distinct cell populations of both the innate (granulocytes, monocytes, NK cells) and the adaptive (T, B, NKT cells) arms of immunity and calculated a series of immune cell ratios to reveal alterations in immune cell composition after COVID-19 resolution. We first analyzed the immune profile of active COVID-19 patients to ensure the performance of our panel; in agreement with previous reports, we detected similar immune cell deficiencies, the most prominent being low T, B, and NK cells, and low granulocytes, as well as increased percentages of Th2-type cells and monocytes [ 5 , 6 , 7 , 8 , 10 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 82%
“…In viral infections, a defective cytotoxicity leads to the accumulation of antigenic stimuli, perpetuating inflammation and triggering tissue damage, and recent studies in COVID-19 patients have reported a decreased NK cell function, including a negative correlation between number of NK cells and IL-6 levels [ 53 ] and a profound depletion of NK cells [ 42 ], especially in severe patients [ 54 ]. IL-6 and IL-10 have the capacity to reduce NK cell cytotoxicity (IL-6 may reduce the expression of perforin and granzyme B while IL-10 negative correlate with NK cell cytotoxicity, through a reduction in IFN- and IL-2 expression) [ 55 , 56 ]. With respect to IL-2R levels, CD25 is expressed by T cells during immune activation and its soluble form (also known as IL-2R), is released into the bloodstream [ 57 ].…”
Section: Haemophagocytic Syndrome Related To Covid-19mentioning
confidence: 99%
“…CD8 + T cells have been indicated as an independent predictor for COVID-19 severity and treatment efficacy [ 8 , 20 , 21 ]. According to Liu and colleagues, decreased CD8 + was directly correlated with pulmonary involvement and pneumonia [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In NK cells, NKG2A leads to the decreased expression of TNFα, IL-2 and IFNγ and reduced granzyme B levels. [ 20 ] Two cytokines, IL-6 and IL-10, highly present in SARS-CoV-2 infections [ 13 ], can reduce NK cell cytotoxicity [ 24 ]. In particular, IL-6 directly reduces the expression of perforin and granzyme B.…”
Section: Discussionmentioning
confidence: 99%